HIV INFECTION AND CARDIOVASCULAR COMPLICATIONS - S. S. Yakushin; E. V. Filippov (Klinicist)
Due to the increasing number of HIV-infected patients and duration of their survival value for cardiovascular disease complications in the structure of HIV is increasing. The article describes the most common complication, developing in this group of patients. Focuses on the tactics of dilated cardiomyopathy and pericardial effusion in HIV-infected patients. Coronary heart disease and its relation to use of antiretroviral drugs and HIV infection are also described.